Searching to combine technologies for safer food attainment - Lucilla Imbroinise Azeredo Caruso (Ciência e Tecnologia de Alimentos, 2011)
Campylobacteriosis is an infection frequently acquired through the consumption of animal origin products. Chicken can be considered the main responsible cause in the transmission chain of this disease. Ionizing radiation was used to verify the reduction of the microbiological load of Campylobacter jejuni present in chicken liver, which, in natura, can present contamination in up to 100% of the cases. The doses of irradiation used were: 0.20 kGy, 0.27 kGy, 0.30 kGy and 0.35 kGy. The samples of chicken liver were acquired in aviaries, local supermarkets and large chain supermarkets. The samples were analyzed for Campylobacter at FIOCRUZ . Irradiation was performed at COPPE/UFRJ, using a Gamma Cell Irradiator with a 60Co gamma source. Only the frozen sample acquired at the local supermarket did not contain the bacterium. Campylobacter sp. was present in all other samples, even when using procedures and technologies that aimed at the impediment of the presence of this bacterium in food and, consequently, at the protection of human health. On the whole, the results were satisfactory; nevertheless, it is known that the bacterial growth conditions required by this bacterium are uncommon when compared to other enteropathogenic bacteria.